(3GdYdGbGJ GdGbJUGOjI GdOhdjI Hjf GdfXQjI hGdJWHjbs - (3QVG(B, (3YHO GdSdGes ((3GdbGgQI(B:s (3GdecJHI GdYUQjI(B,s, 2007)
(3JWhQ GdfXQI ddYdGbGJ GdGbJUGOjI GdOhdjI,GdfXQjGJ hGdJaSjQGJ GdefWbjI ddYdGbGJ GdGbJUGOjI GdOhdjI,GdSjGSGJ GdJLGQjI Hjf GdJMQjQ hGdMeGjI,SYQ GdUQa GdCLfHj,ejRGf GdeOahYGJ,GdBdjGJ GdOhdjI GdefXeI ddYdGbGJ GdGbJUGOjI GdOhdjI,GdGJMGOGJ GdGbJUGOjI GdEbdjejI,GdTQcGJ eJYOOI GdLfSjGJ hXGgQI GdYhdeIs
Keywords: (3GdYdGbGJ GdGbJUGOjI GdOhdjIs